2003
DOI: 10.1590/s0103-50532003000400007
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical determination of 4-nitrophenol by square wave voltammetry on diamond electrodes

Abstract: O comportamento voltamétrico do 4-nitrofenol foi estudado em meio aquoso sobre o eletrodo de diamante dopado com boro usando a voltametria de onda quadrada. Após a otimização dos parâmetros experimentais, o estudo foi realizado em tampão Britton-Robinson com pH 6,0. Nestas condições foi observado somente um pico de oxidação em torno de 1,0 V vs. Ag/AgCl com transferência de dois elétrons e um processo controlado pela adsorção das espécies na superfície do eletrodo. O limite de detecção (LD) obtido foi de 2,8 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 10 publications
1
34
0
8
Order By: Relevance
“…In order to describe these results these authors developed a comprehensive kinetic model that allowed them to predict the trend of the COD and current efficiency for the electrochemical combustion of the organic with BDD electrodes and to estimate the energy consumption during the process. 76,77,110 Other applications of BDD for the destruction and/or determination of organic pollutants were obtained by Avaca and co-workers 105,[131][132][133][134][135][136][137][138][139] where the comparison between the BDD and other anodic materials have permitted use of alternative techniques during the oxidation of the organic pollutants. The BDD electrode is the best choice for several electroanalysis studies, as demonstrated by the electrochemical oxidation of 4-nitrophenol in 0.1 mol L -1 BR buffer electrolyte.…”
Section: Bdd Electrode For Wastewater Treatmentmentioning
confidence: 99%
“…In order to describe these results these authors developed a comprehensive kinetic model that allowed them to predict the trend of the COD and current efficiency for the electrochemical combustion of the organic with BDD electrodes and to estimate the energy consumption during the process. 76,77,110 Other applications of BDD for the destruction and/or determination of organic pollutants were obtained by Avaca and co-workers 105,[131][132][133][134][135][136][137][138][139] where the comparison between the BDD and other anodic materials have permitted use of alternative techniques during the oxidation of the organic pollutants. The BDD electrode is the best choice for several electroanalysis studies, as demonstrated by the electrochemical oxidation of 4-nitrophenol in 0.1 mol L -1 BR buffer electrolyte.…”
Section: Bdd Electrode For Wastewater Treatmentmentioning
confidence: 99%
“…These results stress the need for performing the cathodic pretreatment just before the electrochemical experiments are conducted, in order to ensure reliable and reproducible results. 26 Previous works from our laboratory have shown the direct electroanalytical determination of 4-NP in pure water 27 and contaminated waters, 28 of pentachlorophenol in pure and contaminated waters 29 as well as in a polluted soil, 30 4-chlorophenol in pure water 31 and carbaryl in contaminated waters 32 using in all cases the square wave voltammetry (SWV) technique on BDD electrodes. However, the determination of 4-NP is severely affected by the strong adsorption of the oxidation products requiring frequent cleaning of the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…Esta é uma das técnicas voltamétricas mais usadas no nosso grupo de pesquisa para o desenvolvimento de métodos eletroanalíticos para a detecção de compostos orgânicos 49,[66][67][68] . Esta avaliação foi realizada para a determinação do pesticida metilparation, um composto altamente tóxico, que se adsorve na superfície do eletrodo de DDB 69 .…”
Section: Influência No Transporte De Massaunclassified